A clinimetric analysis of the Hopkins Symptom Checklist (SCL-90-R) in general population studies (Denmark, Norway, and Italy). (3rd July 2016) - Carrozzino, Danilo; Vassend, Olav; Bjørndal, Flemming; Pignolo, Claudia; Olsen, Lis Raabæk; Bech, Per
Abstract: Background : Although the Symptom Checklist (SCL-90-R) is one of the most widely used self-reported scales covering several psychopathological states, the scalability of the SCL-90-R has been found to be very problematic.Aims : We have performed a clinimetric analysis of the SCL-90-R, taking both its factor structure and scalability (i.e. total scale score a sufficient statistic) into account.Methods : The applicability of the SCL-90-R has been found acceptable in general population studies from Denmark, Norway and Italy. These studies were examined with principal component analysis (PCA) to identify the factor structure. The scalability of the traditional SCL-90-R subscales (i.e. somatization, hostility, and interpersonal sensitivity) as well as the affective subscales (i.e. depression and anxiety and ADHD), were tested by Mokken's item response theory model.Results : Across the three general population studies the traditional scaled SCL-90-R factor including 83 items was identified by PCA. The Mokken analysis accepted the scalability of both the general factor and the clinical SCL-90-R subscales under examination.Conclusion : The traditional, scaled, general 83 item SCL-90-R scale is a valid measure of general psychopathology. The SCL-90-R subscales of somatization, hostility, and interpersonal sensitivity as well as the affective subscales of depression, anxiety, and ADHD were all accepted by the Mokken test for scalability, i.e. their total scores are sufficient statistics.